The Impact of ICT on Workplace Burnout: A Case Study from the College of Education for Humanities, University of Mosul - Abdullah, Noor A. (PROSPECTIVE RESEARCHES, 2025)
The research aims to explore the potential of employing Information and Communication Technology (ICT) and its impact on workplace burnout by reviewing studies addressing these two domains and examining their theoretical and practical findings. The study seeks to address the primary question of whether there is a correlation or causal relationship between the independent variable (ICT) and the dependent variable (workplace burnout). To achieve practical results, the study relied on a primary research tool, a questionnaire, distributed to a sample of faculty members at the College of Education for Human Sciences, University of Mosul. Data analysis and hypothesis testing focused on both correlation and causation relationships. Key findings revealed no correlation between the independent variable (ICT) and the dimensions of emotional exhaustion and depersonalization (aspects of workplace burnout). However, a positive correlation was identified between ICT and the personal accomplishment dimension of workplace burnout. Additionally, the study found no causal relationship between the variables, attributed to other factors not included in the research scope. Based on these findings, the study proposed recommendations, including the importance of engaging faculty and staff in decision-making processes, consulting them on achieving their goals, and addressing workplace burnout dimensions due to its significant implications on performance and the negative effects it may have on faculty and staff roles.